The Use of Exergame in a Multiplayer-Supported Virtual Clinic - Öcal, Tu?şad; Baykara, Muhammet; Uzun, Ismail (Institute of Electrical and Electronics Engineers Inc., 2024)
With technological advancements, physical activities among people have decreased, and time spent in front of screens has increased. This situation has negatively affected physical and mental health. Exergame have been developed to support treatment and rehabilitation processes in healthy individuals and those diagnosed with conditions such as Mild Cognitive Impairment (MCI). These games encourage physical activity and make exercises enjoyable, promoting both physical and mental development. For this reason, exergame have become a preferred rehabilitation method among professionals. Additionally, due to the COVID-19 pandemic and current conditions, the need for remote rehabilitation has arisen to facilitate rehabilitation processes. However, it has been predicted that the lack of communication or distance between the specialist and the patient in remote or online rehabilitation could lead to more significant physical and mental problems. To address this issue, a game called Balloon has been developed in a virtual clinic environment using multiplayer and Mediapipe pose recognition libraries, allowing real-time gameplay, sound, and video to be transmitted from the patient to the specialist. Thus, the Balloon game enables specialists to observe their patients throughout the session and conduct remote therapy. © 2024 IEEE.
8th International Symposium on Multidisciplinary Studies and Innovative Technologies, ISMSIT 2024 -- 7 November 2024 through 9 November 2024 -- Ankara -- 204563
Keywords: COVID-19; Exergame; MCI; Mediapipe; Multiplayer Game; Photon; Pose Detection; Remote Rehabilitation; Technological Rehabilitation; Virtual Clinic